Culture from the Inside Out Travel and Meet Yourself - Cornes, ALan (Yarmouth Intercultural Press, 2004)
This text takes a psychological approach to intercultural interactions. The author helps the sojourner to examine his or her own personality traits, both strengths and weaknesses, and how these characteristics may improve one's ability to communicate effectively in a different culture.
Keywords: Intercultural communication. Cultural awareness. Visitors, Foreign. POLITICAL SCIENCE -- Globalization